Pengelolaan Dana Desa Melalui Prinsip Good Village Governance di Desa Suci Kecamatan Karangpawitan Kabupaten Garut - Aprilia, Suci; Susanti, Elisa (BUDGETING : Journal of Business, Management and Accounting, 2024)
This research discusses the management of village funds conducted by the Desa Suci government through the principle of Good Village Governance. The purpose of this study is to describe how Village Fund Management is carried out by the Government of Desa Suci in order to realize optimal village fund management through the application of the principles of Good Village Governance in Desa Suci. The theory used is the theory of Good Village Governance from Haris Fauzi (2023) in theory states the embodiment of Good Village Governance in village financial management through the principles of transparency, participation, and accountability. This study used descriptive qualitative methods. Data collection was used through interviews with the village government, the village consultative body (BPD), village assistants, and TAPMD of 10 people. The results of this study indicate that the management of village funds conducted by the Government of Desa Suci is good but still not optimal. Transparency conducted by the Government of Desa Suci using information media in the form of websites, Billboards, information distributed by each hamlet through RT and RW groups. The embodiment of participation in the form of community aspirations by holding deliberations, and involving the community in the implementation of activities. Accountability carried out by the Government of the sacred village from the planning stage to the accountability stage by conducting village fund management in accordance with procedures, accountable management through reports to the government on it and the village community. Although the management of funds by the Desa Suci government is good, there are still obstacles, namely from the condition of the community, the low capacity of the village apparatus, changing policies and regulations, and limited village funds to realize the needs of the community. Keywords: Accountability, Participation, Transparency, Village Fund, Good Village governance.